The relationship between stock price towards internal and external determinants: Evidence from consumer industry in Malaysia / Nurul Aiza Nadia Abbas - Abbas, Nurul Aiza Nadia (Faculty of Business and Management, 2018)
Institutional investors have become very dominant in the world market today, and their role has been very significant. Institutional investors are generally specialized in the financial institutions, which channel savings collectively on behalf of other investors to achieve a specific objective in terms of limited risk and maximum returns. There are many previous researchers who find a negative correlation between the levels of institutional ownership and the volatility of stock price, depending on the firm's dividend policy. An extreme volatile problem can threaten the smooth functioning of firm's profitability if liquidity dries up or hedging becomes too costly. As a result, the firm will become more vulnerable to risks resulting from tensions in the institutional investors and, especially firm's performance in a high volatility scenario. Therefore, this study will be conducted to analyse whether the firm involved has a good relationship with their investors which may affect towards their financial performance in overall situations.